Secondary mathematics teachers' beliefs and use of instructional strategies that promote problem solving: a case study in male' Maldives - Mohamed, Lawsha (Institute of Education, International Islamic University Malaysia, 2012)
This study examined secondary mathematics teachers' beliefs and use of instructional strategies that promote problem solving. It is a census study conducted in capital city of Maldives, Male' City involving sixty seven secondary mathematics teachers. A self constructed, two part questionnaire was used to determine teachers' beliefs and use of instructional strategies that promote problem solving. It consisted of seven subscales; teachers' self efficacy, importance of problem solving, use of strategies: explaining, sharing, exploring, questioning and coaching and two overall scales; overall belief scale and use of strategies scale. The findings of this study revealed that most of the teachers have strong self efficacy beliefs and strong beliefs about importance of problem solving approach. However teachers had weak beliefs about using technology to promote problem solving where teachers believed that using calculators is not a good habit and computational procedures should not be automatized. The results of teachers' use of strategies that promote problem solving revealed that most of the teachers frequently use these strategies. However, results showed the two least famous s~ategies among the teachers were presenting students with unfamiliar and open ended problems with very little indication of how to sob1e them and providing a set of problems and allowing the students to choose a problem they would like to work on. Furthermore, study also showed that there is no gender difference in beliefs and use of strategies. However, a significant difference was found between nationality of teachers, level of professional training and years of experience and some scales of beliefs and use of strategies. Another major finding of the study is that there is a positive relationship between beliefs and use of instructional strategies that promote problem solving. The study also indicated that a relationship exists between self efficacy, explaining and over all beliefs of teachers and the demographic variables which is gender, nationality, professional training and years of experience.